Factors Affecting the Amount of Investment Loans in Commercial Banks with the Application of Linear Regression Analysis Methods - Khafsah Joebaedi; D Susanti; N Warwah; K Parmikanti; Badrulfalah Badrulfalah (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2019)
Several factors can affect the amount of investment credit issued by the bank. This study discusses the effect of interest rates, inflation rates, capita income, and the number of medium-large industries on the number of investment loans, using the method of linear regression analysis. The independent variables examined to determine the influence of each and all the independent variables on the number of investment loans in commercial banks, namely interest rates, inflation rates, capita income, and the number of medium-large industries using the parameter estimation method, OLS (Ordinary Least Square).